Effects of molten salt temperature and holding time on synthesis of hercynite by molten salt method. Issue 8 (15th April 2022) - Tan, Wendong; Guo, Xiaoshuang; She, Yiming; Li, Hongshan; Lei, Yuan; You, Jiegang; Zhang, Xiaofang; Luo, Xudong
Abstract: Taking flake α-Al2 O3, Fe2 O3 and graphite as raw materials and KCl-K2 SO4 as molten salt medium, the effects of different molten salt temperature and holding time on the synthesis of hercynite by the molten salt method were studied. The results shows that the content of hercynite increases with the increase of molten salt temperature and holding time, and the optimum process condition for synthesis hercynite from KCl-K2 SO4 molten salt is holding at 1000 °C for 6 h. Meanwhile, the micro-morphology of the synthesizes hercynite powder is independent of the micro-morphology of the raw material, indicating that the process of synthesizing hercynite with KCl-K2 SO4 as molten salt medium is dominated by the "dissolution-precipitation" mechanism.